2016
DOI: 10.1387/ijdb.160136se
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of intracerebral hemorrhage (ICH): novel insights from Zebrafish embryos

Abstract: Intracerebral hemorrhage (ICH) is the most severe subtype of stroke. Treatment options are scarce and given the high morbidity and mortality, relatively ineffective. Since patients with ICH may have an unknown heritable component, the need to identify potential risk factors necessitates the use of animal models to elucidate the genetic underpinnings of neurovascular development and, thereby, identify candidate regulatory pathways that are likely to be disrupted in patients with ICH. Zebrafish (Danio rerio) exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…1 A). Because intracerebral hemorrhage is induced in zebrafish by a variety of gene mutations and morpholino-mediated gene knockdown, as well as after treatment with various compounds ( Eisa-Beygi and Rezaei, 2016 ), we were unable to determine the cause of intracerebral hemorrhage at this stage. Instead, based on this lethal phenotype we came up with the strategy of developing in vivo assay for IRE1α inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…1 A). Because intracerebral hemorrhage is induced in zebrafish by a variety of gene mutations and morpholino-mediated gene knockdown, as well as after treatment with various compounds ( Eisa-Beygi and Rezaei, 2016 ), we were unable to determine the cause of intracerebral hemorrhage at this stage. Instead, based on this lethal phenotype we came up with the strategy of developing in vivo assay for IRE1α inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…93 Nevertheless, one of the mammalian studies also revealed the chronic blood-brain barrier disruption and neuroinflammation as part of the impact after the TBI. 94 Intracerebral hemorrhage in larval zebrafish can show spontaneous brain-specific bleeding without any invasive techniques 95,96 and yet still able to better mimic this aspect of the human TBI condition compared to the commonly used rodent models. 97,98 In brief, atorvastatin (ATV), a known substance to cause spontaneous cerebral-specific blood vessel rupture, was solubilized for zebrafish larvae/embryo treatment in an embryo medium-filled petri dish ( Figure 4G) and those exhibiting ICH at 24 h were separated for further analysis.…”
Section: Larval Intracerebral Hemorrhage (Ich) Modelmentioning
confidence: 99%
“…97,98 In brief, atorvastatin (ATV), a known substance to cause spontaneous cerebral-specific blood vessel rupture, was solubilized for zebrafish larvae/embryo treatment in an embryo medium-filled petri dish ( Figure 4G) and those exhibiting ICH at 24 h were separated for further analysis. 95,[99][100][101] Some studies alternately used the "bubblehead" (bbh) mutant zebrafish line which can exhibit spontaneous ICH similar to ATV. 96 Comparison between the two ICH protocols is yet to be discussed, but both manage to achieve similar ICH injuries in the zebrafish larval model.…”
Section: Larval Intracerebral Hemorrhage (Ich) Modelmentioning
confidence: 99%
“…Comparably, the ‘bubblehead’ (bbh) mutant line, which expresses a hypomorphic mutation in the arhgef7 gene, encoding the Rac GEF βpix, also exhibit spontaneous ICH and hydrocephalus within a similar time frame to the ATV model ( Liu et al , 2007 ; ten Klooster et al , 2006 ). ICH is induced through comparable mechanistic defects in both ATV and bbh models ( Eisa-Beygi & Rezaei, 2016 ) ( Supplementary Figure 1 ). Although several groups have utilised these models to study the development and integrity of the cerebrovasculature ( Buchner et al , 2007 ; Huang et al , 2018 ; Li et al , 2017 ; Liu et al , 2007 ; Yang et al , 2017 ), they have not yet been used to study the pathological and neuroinflammatory consequences of bleeding in the zebrafish larval brain in the context of human ICH.…”
Section: Introductionmentioning
confidence: 96%